Histological and Histochemical Studies on the Laryngeal Cavity of Gaddi Seep - Pathak, Virender (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on 26 larynx of Gaddi sheep collected from local slaughter houses. The mucosal surface of laryngeal cavity was made up of thyroid, cricoid and thin leaf like epiglottis cartilages. The mucosal surface was explored by carefully dissecting out the laryngeal cartilages. The tissues were collected from anterior, middle and posterior mucosal wall of larynx. The formalin fixed samples were processed for routine histological procedures. The anterior surface of the epiglottis and the vocal folds were covered by  stratified squamous epithelium. The lining epithelium was very thin at epiglottis, whereas it was thicker at arytenoid. Posterior laryngeal cavity was lined with pseudostratified ciliated columnar epithelium. Lymphatic aggregates were common in submucosal region. The laryngeal glands were more in sheep than the goats.